Pengaruh Bullying terhadap Prestasi Belajar Siswa di MTs Sibolga - Pandapotan Harahap; Fajaruddin Pasaribu; Azwir Aziz; Hasrian Rudi Setiawan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Bullying is a form of aberrant behavior that can occur either knowingly or unconsciously. The increase in bullying instances in schools demonstrates how concerning the stage of education in Indonesia is. The author’s goal in performing this research is to demonstrate the impact of bullying on student learning achievement. A literature review from research journals on the impact of bullying on students learning achievement is used as the method of this research. According to the findings of the inquiry, bullying has a detrimental effect on pupils' achievement in school. Therefore, all teaching staff must collaborate with kids' parents to provide guidance and oversight to prevent bullying from becoming a recurring problem pattern among students.